Pledges to Islamic state : weak and strong alliances - Franco, Joseph (2015)
Pledges of allegiance and obedience are the typical mechanisms used by jihadist groups to create “alliance hubs”, including the Islamic State of Iraq and Syria (ISIS) which is also known as Islamic State (IS). Some of the alliances may have proven strong, while others remain weak and exist in name only.